2017
DOI: 10.1016/j.chest.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Infection in Interstitial Lung Diseases

Abstract: Interstitial lung disease (ILD) comprises an array of heterogeneous parenchymal lung diseases that are associated with a spectrum of pathologic, radiologic, and clinical manifestations. There are ILDs with known causes and those that are idiopathic, making treatment strategies challenging. Prognosis can vary according to the type of ILD, but many exhibit gradual progression with an unpredictable clinical course in individual patients, as seen in idiopathic pulmonary fibrosis and the phenomenon of "acute exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 106 publications
2
57
0
Order By: Relevance
“…Previous studies revealed that declined forced vital capacity (FVC), low diffusing capacity of the lung for carbon monoxide (DLCO), pulmonary hypertension, comorbid coronary artery disease, surgical resection of lung cancers and various infections etc. were found to be risk factors for AE-ILD (29)(30)(31). However, the results were not homogeneous in different studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies revealed that declined forced vital capacity (FVC), low diffusing capacity of the lung for carbon monoxide (DLCO), pulmonary hypertension, comorbid coronary artery disease, surgical resection of lung cancers and various infections etc. were found to be risk factors for AE-ILD (29)(30)(31). However, the results were not homogeneous in different studies.…”
Section: Discussionmentioning
confidence: 88%
“…Application of azithromycin and prophylactic use of co-trimoxazole were found effective in several clinical trials (57-59). Besides, antifibrotic medication, anti-acid therapy, plasma exchange, Polymyxin-B-immobilized fiber column (PMX) and fluid management were as well-found to have potential, yet disputable effect on outcome of AE-ILD patients (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The development of pulmonary fibrosis in our mouse overexpressing TGFβ1 is a proof-of-concept for the critical role of this cytokine in tissue fibrosis 11 . In addition, TGFβ1 may promote exacerbation of pulmonary fibrosis by directly suppressing both the innate and adaptive immune systems leading to enhanced host susceptibility to infection [19][20][21] . Previous studies have shown that high salt concentration impairs host defense mechanisms by suppressing the activity of antimicrobial peptides or by altering the population of immune cells [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae and Staphylococcus species also frequently cause severe pulmonary infections with high in-hospital mortality rate in IPF patients 20,58,61 . Given the growing evidence that alveolar cell apoptosis plays a central role in the pathogenesis and exacerbation of IPF 62 , it is reasonable to speculate that shedding of deadly peptides constitutes an important contribution to the loss of functional lung alveolar cells and to the poor clinical outcome in patients with complications of microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with a markedly lowered FVC and/or significantly impaired carbon monoxide diffusion indicated by T L,CO , a sudden further worsening of these parameters caused by bacterial or viral pneumonia can lead to acute respiratory failure necessitating invasive mechanical ventilation or even a life-threatening condition. Additionally, respiratory infection can be a factor causing an AE-IPF [349][350][351], according to the current definition of this condition [38]. It is associated with high mortality and can occur at any stage of the disease, even in asymptomatic patients who only have radiographic changes [210,352].…”
Section: Commentarymentioning
confidence: 99%